2017
DOI: 10.1371/journal.pone.0182770
|View full text |Cite
|
Sign up to set email alerts
|

Diagnoses, infections and injuries in Northern Syrian children during the civil war: A cross-sectional study

Abstract: BackgroundThe civil war in Syria including the deliberate targeting of healthcare services resulted in a complex humanitarian emergency, seriously affecting children's health. The objectives of this study are to document diagnoses and disease categories in Northern Syrian children after four years of conflict, and to document infectious diseases and injuries in this vulnerable population.MethodsIn a prospective cross-sectional observational sample study conducted in May 2015, healthcare workers registered demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Research from northern Syria found 28.4% of adults had an NCD diagnosis ( Vernier et al., 2019 ). Other studies have explored NCDs among populations known to comprise IDPs but have not explicitly disaggregated displaced from non-displaced populations ( van Berlaer et al., 2017 ; Ansbro et al., 2019 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Research from northern Syria found 28.4% of adults had an NCD diagnosis ( Vernier et al., 2019 ). Other studies have explored NCDs among populations known to comprise IDPs but have not explicitly disaggregated displaced from non-displaced populations ( van Berlaer et al., 2017 ; Ansbro et al., 2019 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…The impact of humanitarian emergencies on a population's health is severe and exacerbated by increases in food insecurity, population displacement, crowding and poor access to water and sanitation, lack of resistance to infection, the physical and psychological effects of weapons and exposure to violence, and the collapse of basic healthcare services (Van Berlaer et al 2017). The impact of humanitarian emergencies on health workers and service provision is also extensive and includes the destruction of health facilities, infrastructure, shortages in drugs and equipment, loss of health staff, and restricted access to healthcare (Van Berlaer et al 2017). Very often during periods of humanitarian crisis, particularly in that of resource-poor settings, we see a catastrophic failure in healthcare provisional services.…”
Section: Enhancing the Interventional Capacity Of Community Health Womentioning
confidence: 99%
“…Another review from six selected countries in the region showed different ranges of wasting (1.1 to 11.8%), stunting (7.3 to 9.3%), and underweight (1.6 to 5.3%) across these countries [13]. In the meantime, there are many children in the region who are suffering from poor nutrition because of war and conflicts, as well as poverty, specifically in Iraq, Syria, Yemen, Palestine, and Afghanistan [21][22][23]. A number of efforts have been made to combat child malnutrition in the region.…”
Section: Introductionmentioning
confidence: 99%